Microwave-activated quaternary ammonium hemicellulose-based paper strength agent, its preparation method and application
Patent Information
- Application Number
- CN202410234757.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-01
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-03-01
AI Technical Summary
[0037]1、以生物质、纸浆废液中的半纤维素为原料,充分考虑环保原则,实现了废弃物资源的再利用,极大的降低了生产成本,具有良好的工业应用价值。
Smart Images

Figure CN118027248B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomass modification and utilization, specifically to a microwave-excited quaternized hemicellulose-based paper reinforcing agent, its preparation method, and its application. Background Technology
[0002] In recent years, with the gradual depletion of fossil resources such as oil and the increasing prominence of environmental pollution, the concept of green and low-carbon development has been gaining popularity. The development of new energy sources and biodegradable materials to replace petroleum materials using renewable resources such as agricultural and forestry biomass has attracted much attention from research and development fields around the world.
[0003] Hemicellulose is the second most abundant chemical component in agricultural and forestry biomass after cellulose, and it is also a major byproduct that is rarely developed and utilized in the papermaking industry. With the reduction of the world's forest area and the increasing requirements for energy conservation and emission reduction, hemicellulose, as a new type of biodegradable polymer material, has become an important research direction in the field of green chemical engineering through modification to maximize its development and utilization.
[0004] Quaternary ammonium polymeric dispersants are the most important type of cationic dispersants. Their molecular chains contain positively charged groups, which make them easy to adsorb negatively charged molecular systems to form a stable adsorption film. This overcomes the shortcomings of inorganic dispersants and small organic molecule dispersants, which are unstable and have poor effects. They play a role in anti-caking, softening, anti-corrosion, sterilization, and antistatic properties, and have become a hot topic in the application and development of various industrial fields. Summary of the Invention
[0005] Purpose of the invention: The technical problem to be solved by the present invention is to address the shortcomings of the prior art by providing a microwave-excited quaternized hemicellulose-based paper reinforcing agent, its preparation method and application.
[0006] To solve the above-mentioned technical problems, the present invention discloses the following technical solution:
[0007] In a first aspect, the present invention discloses a quaternized modified hemicellulose.
[0008] The quaternized modified hemicellulose is prepared by the following method: (1) the hemicellulose, alkaline catalyst and metal oxide are activated under microwave radiation; (2) the hemicellulose is then modified with a quaternary ammonium salt cationic etherifying agent to obtain a reaction solution containing quaternized modified hemicellulose.
[0009] Secondly, the present invention discloses a method for preparing quaternized modified hemicellulose, namely the method for preparing quaternized modified hemicellulose described in the first aspect above.
[0010] The preparation method includes: (1) activating hemicellulose, alkaline catalyst and metal oxide under microwave radiation; (2) modifying with quaternary ammonium salt cationic etherifying agent to obtain a reaction solution containing quaternized ammonium modified hemicellulose.
[0011] In the first and second aspects mentioned above,
[0012] In step (1), the hemicellulose is pre-activated under microwave radiation. Specifically, the hemicellulose is dispersed in a solvent, microwave-heated, cooled to room temperature, and then an alkaline catalyst and metal oxide are added. More specifically, the hemicellulose is added to a solvent and microwave-heated to make it uniformly dispersed in the solvent. After cooling to room temperature, an alkaline catalyst and metal oxide are added to the hemicellulose suspension to activate the modified groups through nucleophilic reaction.
[0013] The alkaline catalyst includes lithium hydroxide, sodium hydroxide, potassium hydroxide, triethylamine, pyridine, imidazole, or any combination thereof; preferably lithium hydroxide, sodium hydroxide, potassium hydroxide, or any combination thereof; preferably sodium hydroxide.
[0014] The metal oxide includes magnesium oxide, chromium oxide, iron oxide, cobalt oxide, copper oxide, zinc oxide, ferrous oxide, or any combination thereof; preferably copper oxide, magnesium oxide, iron oxide, cobalt oxide, or any combination thereof; preferably copper oxide.
[0015] The solvent for the activation treatment includes water, ethanol, isopropanol, dimethyl sulfoxide, 1,4-dioxane, or any combination thereof.
[0016] The temperature of the microwave is 60-110℃, preferably 70-100℃, and more preferably 80-90℃; the duration of the microwave is 4-60 min, preferably 7-40 min, and more preferably 10-20 min.
[0017] The mass-to-volume ratio of hemicellulose to solvent is 1g:5-35mL, preferably 1g:10-30mL, and more preferably 1g:15-25mL.
[0018] The mass ratio of the alkaline catalyst to hemicellulose is 0.05-2:1, preferably 0.2-1:1.
[0019] The mass of the metal oxide is 1%-15% of the mass of the alkaline catalyst, preferably 2%-10%.
[0020] The activation temperature is 25-60℃, preferably 30-50℃, and more preferably 35-45℃; the activation time is 4-45 min, preferably 7-35 min, and more preferably 15-25 min.
[0021] In step (2),
[0022] The quaternary ammonium salt type cationic etherifying agent includes 3-chloro-2-hydroxypropyltrimethylammonium chloride, 2,3-epoxypropyltrimethylammonium chloride, allyltrimethylammonium chloride, 3-bromopropyltrimethylammonium bromide, allyltrimethylammonium bromide, or any combination of the foregoing.
[0023] The mass ratio of the quaternary ammonium salt cationic etherifying agent to hemicellulose is 0.1-5:1, preferably 1-4:1, and more preferably 2-3:1; preferably, the quaternary ammonium salt cationic etherifying agent is added to the reaction system in the form of a quaternary ammonium salt cationic etherifying agent solution; preferably, the solvent of the quaternary ammonium salt cationic etherifying agent solution is water, ethanol, isopropanol, dimethyl sulfoxide, 1,4-dioxane, or any combination of the foregoing.
[0024] The solid-liquid ratio of the quaternization modification reaction system is 1g:10-50mL, preferably 1g:15-40mL, and more preferably 1g:20-30mL.
[0025] The quaternization modification temperature is 30-80℃, preferably 40-75℃, and more preferably 50-70℃; the reaction time is 0.4-5h, preferably 0.6-3h, and more preferably 0.8-1.2h.
[0026] In step (2), after the reaction is completed, the resulting reaction solution is separated by membrane separation to obtain a concentrated solution containing quaternized modified hemicellulose.
[0027] The membrane separation component of the membrane includes any one of hollow fiber membrane, plate membrane, spiral wound membrane, and tubular membrane, with tubular membrane being preferred.
[0028] The concentrated liquid contains more than 2 wt% solids, such as 5 wt%, 10 wt%, 15 wt%, 25 wt%, 30 wt%, 35 wt%, etc.
[0029] Thirdly, the present invention discloses a paper strengthening agent.
[0030] The paper strengthening agent includes the quaternized modified hemicellulose described in the first aspect above or the quaternized modified hemicellulose prepared by the method described in the second aspect above.
[0031] Fourthly, the present invention discloses the application of the quaternized modified hemicellulose described in the first aspect or the quaternized modified hemicellulose prepared by the method described in the second aspect as a paper reinforcing agent in the preparation of paper.
[0032] The hemicellulose described in this invention is derived from biomass, including but not limited to wheat straw, corn straw, cotton straw, rice straw, bagasse, corn cob, eucalyptus, acacia, beech, as well as pulp and paper waste liquor, chemical fiber waste liquor, pulp waste liquor, viscose fiber waste liquor, etc., and is any one of xylan, mannan, xyloglucan hemicellulose, wherein xylan hemicellulose is preferred, and hemicellulose with a xylan content of 75 wt% or more is preferred, such as 80 wt%, 85 wt%, or 90 wt%.
[0033] The degree of substitution of the quaternized modified hemicellulose prepared by the above method is 0.01-0.50. The reaction principle equation is shown below:
[0034]
[0035] The microwave-excited quaternized hemicellulose-based paper strengthening agent provided by this invention reasonably solves the problem of reusing hemicellulose plant resources. The preparation method is simple to operate, the quaternization reaction is fast, the modified hemicellulose has a moderate degree of substitution, and has chemical properties similar to cationic starch. It has excellent dispersion and strengthening properties for papermaking, greatly reduces the production cost, and has good practical industrial application value.
[0036] Beneficial effects:
[0037] 1. Using hemicellulose from biomass and pulp waste as raw materials, this method fully considers environmental protection principles, realizes the reuse of waste resources, greatly reduces production costs, and has good industrial application value.
[0038] 2. By using microwave radiation as a heat source and adding metal oxides in conjunction with liquid alkali to pretreat hemicellulose, the activity of hemicellulose groups is greatly improved, the quaternization reaction rate is fast and the degree of substitution is increased, resulting in excellent dispersibility and reinforcing properties for papermaking.
[0039] 3. Membrane separation is used to treat the modified solution. The operation process is simple and can effectively recover and recycle alkaline solution and unreacted etherifying agent. Attached Figure Description
[0040] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments, and the advantages of the present invention in the above and / or other aspects will become clearer.
[0041] Figure 1 For the source of viscose fiber waste liquid hemicellulose 13 C10 NMR spectrum.
[0042] Figure 2 The quaternized hemicellulose in Example 1 13 C10 NMR spectrum.
[0043] Figure 3 The quaternized hemicellulose in Example 11 13 C10 NMR spectrum. Detailed Implementation
[0044] Unless otherwise specified, the experimental methods described in the following examples are conventional methods; the reagents and materials described are commercially available unless otherwise specified.
[0045] The hemicellulose used in this embodiment of the invention is a solid powder obtained by spray drying after concentration and separation of viscose fiber waste liquid through nanofiltration membrane. The xylan content is 89.12 wt%. The NMR of the obtained hemicellulose is as follows: Figure 1 As shown.
[0046] In the following examples, the degree of substitution of the quaternized hemicellulose was obtained by Vario Micro elemental analysis to determine the ratio of carbon content (C) to nitrogen content (N), where the carbon content and nitrogen content are mass percentages and are calculated according to the following formula:
[0047] DS=(60.05×N) / (14.01×C-72.06×N)
[0048] Unless otherwise specified, the microwave heating power in the following embodiments is 600W; the cooling is to room temperature unless otherwise specified; the tubular membrane has a molecular weight cutoff of 3000Da unless otherwise specified, and the reaction solution is specifically concentrated to a solid content of 10wt% for later use.
[0049] Example 1
[0050] 50g of hemicellulose was uniformly dispersed in 1000mL of pure water and microwaved at 85℃ for 15min. Then, the mixture was cooled and 30g of sodium hydroxide and 1.5g of copper oxide were added. After dissolving and mixing, the mixture was microwaved at 40℃ for 20min. At the end of the reaction, 208g of 60wt% 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution was slowly added, and the solid-liquid ratio was adjusted to 1:25g / mL (i.e., 167mL of pure water was added). Microwave modification was continued at 60℃ for 1h. After cooling to room temperature, the reaction solution was concentrated and purified using a tubular membrane to obtain 616g of concentrated solution containing quaternized modified hemicellulose. A small amount was dried and its degree of substitution was determined to be 0.50. The NMR of the obtained quaternized modified hemicellulose was as follows: Figure 2 As shown.
[0051] Example 2-10
[0052] Similar to Example 1, except that the type of alkaline catalyst or metal oxide was changed, and the specific results are shown in Table 1.
[0053] Table 1
[0054]
[0055]
[0056] Comparative Example 1
[0057] 50g of hemicellulose was uniformly dispersed in 1000mL of pure water and heated in an oil bath at 85℃ for 15min. Then, the mixture was cooled and 30g of sodium hydroxide and 1.5g of copper oxide were added. After dissolving and mixing, the mixture was activated in an oil bath at 40℃ for 20min. After the reaction was complete, 208g of 60wt% 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution was slowly added, and the solid-liquid ratio was adjusted to 1:25g / mL by adding 167mL of pure water. The modification was continued in an oil bath at 60℃ for 1h. After cooling to room temperature, the reaction solution was concentrated and purified using a tubular membrane to obtain 522g of concentrated solution containing quaternized modified hemicellulose. A small amount was dried and its degree of substitution was determined to be 0.26.
[0058] Comparative Example 2
[0059] 50g of hemicellulose was uniformly dispersed in 1000mL of pure water and heated in an oil bath at 85℃ for 15min. Then, 30g of sodium hydroxide was added after cooling and the mixture was dissolved and stirred. The mixture was then activated in an oil bath at 40℃ for 20min. After the reaction was complete, 208g of 60wt% 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution was slowly added, and the solid-liquid ratio was adjusted to 1:25g / mL by adding 167mL of pure water. The modification was continued in an oil bath at 60℃ for 1h. After the reaction was completed, the mixture was cooled to room temperature, and the reaction solution was finally concentrated and purified using a tubular membrane to obtain 503g of concentrated solution containing quaternized modified hemicellulose. A small amount was dried and its degree of substitution was determined to be 0.23.
[0060] Comparative Example 3
[0061] 50g of hemicellulose was uniformly dispersed in 1000mL of pure water and heated in an oil bath at 85℃ for 15min. Then, 1.5g of copper oxide was added after cooling and mixing, followed by activation in an oil bath at 40℃ for 20min. After the reaction was complete, 208g of 60wt% 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution was slowly added, and the solid-liquid ratio was adjusted to 1:25g / mL by adding 167mL of pure water. Modification was continued in an oil bath at 60℃ for 1h. After cooling to room temperature, the reaction solution was concentrated and purified using a tubular membrane to obtain 459g of concentrated solution containing quaternized modified hemicellulose. A small amount was dried, and the degree of substitution was found to be almost 0.
[0062] Comparative Example 4
[0063] 50g of hemicellulose was uniformly dispersed in 1000mL of pure water and microwaved at 85℃ for 15min. Then, 30g of sodium hydroxide was added after cooling and the mixture was dissolved and stirred. The mixture was then microwaved at 40℃ for 20min. After the reaction was complete, 208g of 60wt% 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution was slowly added, and the solid-liquid ratio was adjusted to 1:25g / mL (167mL of pure water was added). Microwave modification was continued at 60℃ for 1h. After cooling to room temperature, the reaction solution was concentrated and purified using a tubular membrane to obtain 577g of concentrated solution containing quaternized modified hemicellulose. A small amount was dried and its degree of substitution was determined to be 0.39.
[0064] Examples 11-16
[0065] Similar to Example 1, except for changes in the amount of sodium hydroxide or the quaternization modification time. Specific results are shown in Table 2. In Example 11, the NMR of the obtained quaternized modified hemicellulose is as follows: Figure 3 As shown.
[0066] Table 2
[0067] 1 30 1 616 0.50 11 10 1 461 0.13 12 50 1 485 0.29 13 30 0.5 578 0.34 14 40 0.5 570 0.38 15 20 2 545 0.25 16 30 2 572 0.42
[0068] Examples 17-24
[0069] Similar to Example 1, except that the type of solvent or quaternary ammonium salt cationic etherifying agent was changed, and the specific results are shown in Table 3.
[0070] Table 3
[0071]
[0072]
[0073] Example 25
[0074] 50g of hemicellulose was uniformly dispersed in 1000mL of pure water and microwaved at 85℃ for 15min. Then, 20g of sodium hydroxide and 1g of copper oxide were added after cooling and dissolved. The mixture was then microwaved at 40℃ for 20min. After the reaction was complete, 167g of 60wt% 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution was slowly added, and the solid-liquid ratio was adjusted to 1:25g / mL (i.e., 183mL of pure water was added). Microwave modification was continued at 60℃ for 1h. After cooling to room temperature, the reaction solution was concentrated and purified using a tubular membrane to obtain 451g of concentrated solution containing quaternized modified hemicellulose. A small amount was dried and its degree of substitution was determined to be 0.10.
[0075] Commercially available starch-based paper strengthening agents YZ-121F, YZ-122, and YZ-139, with a solid content of 10 wt%, were prepared and gelatinized separately with a concentrated solution containing quaternized ammonium-modified hemicellulose. These gelatinized agents were then added to pulp after being disintegrated using a fiber dissociator at 20,000 rpm. After stirring and reacting for a period of time, the paper was formed, and its various physical properties were measured according to the national standard for corrugated base paper. At this point, the actual pulp concentration was 0.55%. The specific results of the paper strength are detailed in Table 4. The results indicate that the quaternized ammonium-modified hemicellulose has an effect comparable to commercially available starch-based paper strengthening agents and can effectively improve the strength of the corresponding paper.
[0076] Table 4
[0077]
[0078] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A method for preparing quaternized modified hemicellulose, characterized in that, include: Hemicellulose was dispersed in water, microwaved and heated, then cooled to room temperature. Sodium hydroxide and copper oxide were added as alkaline catalysts, and the mixture was activated under microwave radiation at 35-45℃ for 15-25 min. Then, it was modified with an aqueous solution of 3-chloro-2-hydroxypropyltrimethylammonium chloride, a quaternary ammonium salt-type cationic etherifying agent, at 50-70℃ for 0.8-1.2 h to obtain a reaction solution containing quaternized modified hemicellulose. The mass-to-volume ratio of hemicellulose to water is 1g:5-35mL; the mass ratio of the alkaline catalyst to hemicellulose is 0.2-1:1; the mass of the metal oxide is 2%-10% of the mass of the alkaline catalyst; the mass ratio of the quaternary ammonium salt-type cationic etherifying agent to hemicellulose is 2-3:1; and the solid-liquid ratio of the quaternization-modified reaction system is 1g:10-50mL.
2. The preparation method according to claim 1, characterized in that, The mass-to-volume ratio of hemicellulose to water is 1g:10-30mL.
3. The preparation method according to claim 1, characterized in that, The mass-to-volume ratio of hemicellulose to water is 1g:15-25mL.
4. The preparation method according to claim 1, characterized in that, The solid-liquid ratio of the quaternization modification reaction system is 1g:15-40mL.
5. The preparation method according to claim 1, characterized in that, The solid-liquid ratio of the quaternization modification reaction system is 1g:20-30mL.
6. The preparation method according to claim 1, characterized in that, The resulting reaction solution was separated by membrane separation to obtain a concentrated solution containing quaternized modified hemicellulose.
7. A paper strengthening agent, characterized in that, This includes quaternized modified hemicellulose prepared by the method described in any one of claims 1-6.
8. The use of the quaternized modified hemicellulose prepared by the method of any one of claims 1-6 or the paper strengthening agent of claim 7 in the preparation of paper.